2018
DOI: 10.6004/jadpro.2018.9.6.4
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Treatments for Lung Cancer Patients Receiving Hemodialysis

Abstract: Chemotherapy, and now targeted therapies and immunotherapies, are widely used for the management of patients with all stages of lung cancer. Some challenges present when patients are receiving concomitant hemodialysis for various comorbid conditions. However, this should not immediately rule out a patient for treatment. Many drugs may be safely given to patients who are receiving hemodialysis with the proper dosing schedule and careful monitoring. This article will outline the current literature surrounding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…It is believed that the reduction in the initial dose of topotecan by 50–75% is recommended for ESRD patients on non-HD days or after the HD session. 9 …”
Section: General Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that the reduction in the initial dose of topotecan by 50–75% is recommended for ESRD patients on non-HD days or after the HD session. 9 …”
Section: General Considerationsmentioning
confidence: 99%
“…The plasma concentrations of etoposide were comparable to those of patients with normal renal function. 9 A 30-year-old patient on HD with poor risk metastatic non-seminomatous germ cell tumor received five cycles of full dose of cisplatin and 60% dose of etoposide on days 1–5, every 21 days and strategically timed with HD. Some studies have indicated that standard-dose chemotherapy with etoposide is feasible and effective in patients undergoing hemodialysis.…”
Section: General Considerationsmentioning
confidence: 99%